2022
DOI: 10.3389/fpubh.2022.989519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an 8-week Baduanjin intervention combined with low-carbohydrates diet among overweight people who struggle with drug addiction

Abstract: BackgroundPrior studies have consistently revealed that a combination of physical activity with caloric restriction results in a reduction in body weight in the general population. Both overweight and drug abuse are risk factors for poor physiological health, and poor mental health has been associated with drug abuse and unhealthy body mass index (BMI). However, the effects of low-carbohydrates diet (LC) combined with mind-body exercise intervention on improving anthropometric characteristics, lipid metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…After carefully reviewing the titles and abstracts, an additional 13 articles were eliminated. A comprehensive evaluation was conducted on a total of 35 articles, among which 10 were included in this meta-analysis (29)(30)(31)(32)(33)(34)(35)(36)(37)(38). There were no additional studies identified through manual search.…”
Section: Retrieved Resultsmentioning
confidence: 99%
“…After carefully reviewing the titles and abstracts, an additional 13 articles were eliminated. A comprehensive evaluation was conducted on a total of 35 articles, among which 10 were included in this meta-analysis (29)(30)(31)(32)(33)(34)(35)(36)(37)(38). There were no additional studies identified through manual search.…”
Section: Retrieved Resultsmentioning
confidence: 99%
“…Yoga emphasizes physical postures, breathing exercises, and meditation to promote flexibility, strength, balance, and mental well-being. [24,25] Tai chi involves slow and controlled movements, deep breathing, and mental focus to promote balance, flexibility, and relaxation. [26,27] Breathing training specifically focuses on improving breathing techniques to enhance respiratory function and promote relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…After carefully reviewing the titles and abstracts, an additional 13 articles were eliminated. A comprehensive evaluation was conducted on a total of 35 articles, among which 10 were included in this meta-analysis (29)(30)(31)(32)(33)(34)(35)(36)(37)(38). There were no additional studies identified through manual search.…”
Section: Retrieved Resultsmentioning
confidence: 99%